ISLAMIC-BASED GROUP GUIDANCE TO DEVELOP INDEPENDENCE IN VISUALLY IMPAIRED ADOLESCENTS AT THE PALEMBANG SENSORY DISABILITY CENTER - Sabrina, Junita; Jannati, Zhila; Assoburu, Selvia (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to determine the picture of independence in blind adolescents before and after being given Islamic-based group guidance and to determine the implementation of Islamic-based group guidance to develop independence in blind adolescents at the Palembang sensory disability home. This study uses a descriptive qualitative research method, while data collection techniques are observation, interviews, and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and conclusions. The subjects taken were 8 people with sensory disability. The results of this study found that the picture of independence before being given Islamic-based group guidance was that adolescents tended to depend on others and lacked initiative in worship. Group guidance was carried out in four stages, namely the beginning, transition, work, and end. After being given Islamic-based group guidance, the results showed that Islamic-based group guidance was effective in developing independence and quality of life for blind people as a step towards a better life.